Task Decomposition Training and Freestyle Stroke Efficiency Among Swimming Athletes in an Institute of Technology in Sichuan, China - Wang, Binxin (Pacific International Journal, 2025)
This study examines the relationship between task decomposition training (TDT) and freestyle stroke efficiency among competitive swimmers at a technological institute in Sichuan, China. TDT, which breaks complex strokes into manageable components, has emerged as a critical methodology for enhancing technical precision and performance in aquatic sports. The research employed a descriptive-comparative-correlational design, surveying athletes on their TDT experiences and self-assessed stroke efficiency across multiple dimensions including body alignment, arm mechanics, kick efficiency, and breathing technique. Findings indicate that TDT significantly improves swimmers’ technical understanding and execution, with notable enhancements in stroke timing, coordination, and hydrodynamics. However, areas such as body position alignment and energy efficiency showed room for improvement. The study reveals a strong positive correlation between structured TDT implementation and overall stroke efficiency, particularly among experienced athletes. These results underscore the value of systematic skill decomposition in swimming pedagogy and provide a foundation for developing targeted training protocols that can optimize athletic performance for competitive swimmers across different experience levels.